On small Lebesgue spaces - Claudia Capone; Alberto Fiorenza (Journal of Function Spaces and Applications)
We consider a generalized version of the small Lebesgue spaces, introduced in [5] as the associate spaces of the grand Lebesgue spaces. We find a simplified expression for the norm, prove relevant properties, compute the fundamental function and discuss the comparison with the Orlicz spaces.